A Comprehensive Analysis Reveals Mutational Spectra and Common Alleles in Chinese Patients with Oculocutaneous Albinism - Wei, Aihua; Wang, Yu; Long, Yan; Wang, Yi; Guo, Xiaoli; Zhou, Zhiyong; Zhu, Wei; Liu, Juntao; Bian, Xuming; Lian, Shi; Li, Wei (Journal of investigative dermatology, 2010)
Oculocutaneous albinism (OCA) is a heterogeneous recessive disorder with hypopigmentation in the skin, hair, and eyes. At least 16 genes have been identified as causative genes for human OCA. No comprehensive analysis has been conducted to study the spectral distribution of OCA in Chinese patients. We screened 127 unrelated and unselected Chinese OCA patients for mutations in the TYR, OCA2, TYRP1, SLC45A2, and HPS1 genes. We found that the spectrum of mutational genes and alleles of OCA is population specific. OCA1 is the most common (70.1% of cases) form of Chinese OCA, whereas OCA2, OCA4, and HPS1 account for 10.2%, 12.6%, and 1.6%, respectively. No apparent pathological mutation of TYRP1 has been found. Thirty-eight previously unreported mutational alleles were identified from these OCA patients and were not found in 100 nonalbinism subjects. Of the TYR mutational alleles, 81.1% were clustered on exons 1 and 2. Ten common alleles account for 74.6% of the mutational TYR alleles in Chinese OCA1 patients. The p.D160H allele accounts for 55.6% of the mutational SLC45A2 alleles in Chinese OCA4 patients. These results provide useful information for the establishment of an optimized strategy of gene diagnosis and genetic counseling of Chinese OCA patients.